Identification of Novel Craniofacial Regulatory Domains Located far Upstream of SOX9 and Disrupted in Pierre Robin Sequence. Issue 8 (August 2014) - Gordon, Christopher T.; Attanasio, Catia; Bhatia, Shipra; Benko, Sabina; Ansari, Morad; Tan, Tiong Y.; Munnich, Arnold; Pennacchio, Len A.; Abadie, Véronique; Temple, I. Karen; Goldenberg, Alice; van Heyningen, Veronica; et al.
<x xml:space="preserve">Abstract</x> The craniofacial regulatory potential of non‐coding DNA upstream of SOX9 has not been fully mapped. ChIP‐Seq analysis led to the identification of candidate SOX9 craniofacial enhancers. In transgenic zebrafish embryos, one of these elements, peak 17, drove expression of a GFP reporter gene in the pharyngeal arches. This element falls with deletions observed in Pierre Robin sequence (PRS) patients; loss of the element in these patients may result in abnormal expression of SOX9, leading to the craniofacial phenotype of PRS. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>